Development Using Higher Order Thinking Skills Assisted by Quizizz Applications in Science Learning - Deden Dicky Dermawan; Sri Wardani; Yuli Kurniawati Sugiyo Pranoto (Universitas Negeri Semarang, 2021)
The purpose of this study is to develop a valid, reliable, feasible, and practical test instrument based on Higher Order Thinking Skill (HOTS) for grade V elementary school science learning theme 8 The environment of our friends. This research technique combines R&D with an ADDIE research design (analysis, design, development, implementation, and evaluation). Design, expert validation, small-scale trials, and large-scale trials are all steps developed. The instrument created is a multiple-choice instrument that makes use of the Quizizz application. The data collection technique used in this development research is a multiple-choice test and a questionnaire on practicality. The results of the validation of the HOTS-based multiple-choice test instrument are valid. The reliability coefficient for the limited-scale trial was 0.648, while the reliability coefficient for the large-scale trial was 0.762, indicating that the instrument is reliable. A practicality questionnaire was developed with four raters who demonstrated very practical requirements.